The Outcome of Patients with Triple Negative Breast Cancer: The Turkish Oncology Group Experience - Eralp, Yesim; Kilic, Leyla; Alco, Gul; Basaran, Gul; Dogan, Mutlu; Dincol, Dilek; Haydaroglu, Ayfer (Aves, 2014)
Objective:Triple negative breast cancer (TNBC) is generally considered as a poorer prognostic subgroup, with propensity for earlier relapse and visceral involvement. The aim of this study is to evaluate the outcome of non-metastatic TNBC patients from different centers in Turkey and identify clinical and pathologic variables that may effect survival. Materials and Methods:Between 1993-2007, from five different centers in Turkey, 316 nonmetastatic triple negative breast cancer patients were identified with follow-up of at least 12 months. The data was collected retrospectively from patient charts. The prognostic impact of several clinical variables were evaluated by the Kaplan-Meier and Cox multivariate anayses. Results:Mean age at diagnosis was 49 years (range:24-82). The majority of the patient group had invasive ductal carcinoma (n:260, 82.3%) and stage II disease (n:164; 51.9%). Majority of the patients (87.7%) received adjuvant chemotherapy. 5 year overall survival (OS) and disease-free survival (DFS) rates were 84.6% and 71.6%, respectively. Univariate analysis revealed locally advanced disease (p:0.001), advanced pathological stage (p:0.021), larger tumor size (T1&T2 vs T3&T4) (p< 0.001), nodal positivity (p:0.006), and extensive nodal involvement (p< 0.001) as significant factors for DFS; whereas, advanced pathological stage (p:0.017), extensive nodal involvement (p< 0.001) and larger tumor size (p:0,001) and presence of breast cancer-affected member in the family (p=0.05) were identified as prognostic factors with an impact on OS. Multivariate analysis revealed larger tumor size (T3&T4 vs T1&T2) and presence of lymph node metastases (node-positive vs node-negative) as significant independent prognostic factors for DFS (Hazard ratio (HR):3.03, 95% CI:1.71-5.35, p< 0.001 and HR:1.77, 95% CI:1.05-3.0, p=0.03, respectively). Higher tumor stage was the only independent factor affecting overall survival (HR:2.81; 95% CI, 1.27-6.22, p=0.01). Conclusion:The outcome of patients with TNBC in this cohort is comparable to other studies including TNBC patients. Tumor size and presence of lymph node metastasis are the major independent factors that have effect on DFS, however higher tumor stage was the only negative prognostic factor for OS.
Keywords: Triple-negative; breast cancer; prognosis; survival